Determination of deep and shallow levels in conjugated polymers by electrical methods - Stallinga, Peter (2015)
Conjugated organic semiconductors have been submitted to various electrical measurement techniques in order to reveal information about shallow levels and deep traps in the forbidden gap. The materials consisted of poly[2-methoxy, 5 ethyl (2' hexyloxy) paraphenylenevinylene] (MEH-PPV), poly(3-methylthiophene) (PMeT), and alpha-sexithienyl (alpha T6) and the employed techniques were IV, CV, admittance spectroscopy, TSC, capacitance and current transients. (C) 1999 Elsevier Science B.V. All rights reserved.